Study on the Stability of Unbalanced Rotation of Large-Tonnage T-Shaped Rigid Frame Bridges - Hantao Wu; Zheng Yang; Chunting Lu; Zhongming Li; Chen Guo; Guohua Sha (Buildings, 2024)
In the design of cantilever method bridge anti-overturning structures, the appropriate gap between the supporting foot and the lower rotating table is a crucial factor. It affects the distribution of the upper load and the friction force of the rotating structure, playing a key role in stability control. Currently, a reasonably defined range for this gap based on engineering practice has not been established. This study, set against the backdrop of practical engineering for large-tonnage rotational bridges, analyzes potential overturning instability forms during rotation. It provides a detailed examination of the stability performance of bridges in unbalanced states under single-side joint support configurations and analyzes the mechanical performance and stability under different gaps and impact velocities during rotation. The result is that the impact acceleration, angular acceleration of rotation, and tilt angle (gap) increase displacement and stress in the support system, posing a significant safety risk. The present research demonstrates the safety and rationality of the proposed unbalanced rotation and provides control limits for tilt angle and rotation acceleration during the rotation process. These results demonstrate that the proposed support mode ensures safety requirements during unbalanced rotation, offering insights for the design and construction of large-tonnage rotational bridges.